A systematic evaluation of the error detection abilities of a new diode transmission detector. Issue 9 (5th August 2019) - Sarkar, Vikren; Paxton, Adam; Kunz, Jeremy; Szegedi, Martin; Nelson, Geoff; Rassiah‐Szegedi, Prema; Zhao, Hui; Huang, Y. Jessica; Su, Frances; Salter, Bill J.
Abstract: Transmission detectors meant to measure every beam delivered on a linear accelerator are now becoming available for monitoring the quality of the dose distribution delivered to the patient daily. The purpose of this work is to present results from a systematic evaluation of the error detection capabilities of one such detector, the Delta 4 Discover. Existing patient treatment plans were modified through in‐house‐developed software to mimic various delivery errors that have been observed in the past. Errors included shifts in multileaf collimator leaf positions, changing the beam energy from what was planned, and a simulation of what would happen if the secondary collimator jaws did not track with the leaves as they moved. The study was done for simple 3D plans, static gantry intensity modulated radiation therapy plans as well as dynamic arc and volumetric modulated arc therapy (VMAT) plans. Baseline plans were delivered with both the Discover device and the Delta 4 Phantom+ to establish baseline gamma pass rates. Modified plans were then delivered using the Discover only and the predicted change in gamma pass rate, as well as the detected leaf positions were evaluated. Leaf deviations as small as 0.5 mm for a static three‐dimensional field were detected, with this detection limit growing to 1 mm with more complex delivery modalities such as VMAT. The gamma pass rates dropped noticeably once the intentional leaf error introduced was greater than the distance‐to‐agreement criterion. The unit also demonstrated the desired drop in gamma pass rates of at least 20% when jaw tracking was intentionally disabled and when an incorrect energy was used for the delivery. With its ability to find errors intentionally introduced into delivered plans, the Discover shows promise of being a valuable, independent error detection tool that should serve to detect delivery errors that can occur during radiotherapy treatment.